Towards efficient concrete structures with ultra-thin 3D printed formwork: exploring reinforcement strategies and optimisation - Gebhard, Lukas; Burger, Joris; Mata-Falcón, Jaime; Lloret Fritschi, Ena; Gramazio, Fabio; Kohler, Matthias; Kaufmann, Walter (Virtual and physical prototyping, 2022)
The Eggshell fabrication process combines the 3D printing of formwork with the simultaneous casting of a fast-hardening concrete. One limiting factor to reaching mass-market adoption is a suitable reinforcing strategy. In this study, a reinforcement strategy combining steel reinforcing bars with steel fibres is explored. A series of eight beams were produced using the Eggshell process or conventionally cast. The longitudinal reinforcement was provided by two reinforcing bars, and two types of fibres, either mixed with the concrete or placed and aligned between the cast concrete layers, were used as shear reinforcement. The results showed that combining conventional longitudinal reinforcement and fibres as shear reinforcement is a suitable strategy. These findings were applied to fabricate an optimised beam with a volume reduction of almost 50%. The structural performance of this beam was similar to the beam with a rectangular cross-section with the same reinforcement strategy showing the potential of Eggshell in combination with an innovative reinforcement strategy to produce material-efficient structural concrete elements.